A simple field method to identify foot strike pattern during running - Giandolini, M.; Poupard, T.; Gimenez, P.; Horvais, N.; Millet, G. Y.; Morin, J.-B.; Samozino, P. (Journal of Biomechanics, 2014)
Identifying foot strike patterns in running is an important issue for sport clinicians, coaches and footwear industrials. Current methods allow the monitoring of either many steps in laboratory conditions or only a few steps in the field. Because measuring running biomechanics during actual practice is critical, our purpose is to validate a method aiming at identifying foot strike patterns during continuous field measurements. Based on heel and metatarsal accelerations, this method requires two uniaxial accelerometers. The time between heel and metatarsal acceleration peaks (THM) was compared to the foot strike angle in the sagittal plane (afoot) obtained by 2D video analysis for various conditions of speed, slope, footwear, foot strike and state of fatigue. Acceleration and kinematic measurements were performed at 1000Hz and 120Hz, respectively, during 2-min treadmill running bouts. Significant correlations were observed between THM and afoot for 14 out of 15 conditions. The overall correlation coefficient was r=0.916 (P<0.0001, n=288). The THM method is thus highly reliable for a wide range of speeds and slopes, and for all types of foot strike except for extreme forefoot strike during which the heel rarely or never strikes the ground, and for different footwears and states of fatigue. We proposed a classification based on THM: FFS<-5.49ms<MFS<15.2ms<RFS. With only a few precautions being necessary to ensure appropriate use of this method, it is reliable for distinguishing rearfoot and non-rearfoot strikers in situ.